The impact of Holocene deglaciation and glacial dynamics on the landscapes and geomorphology of Potter Peninsula, King George Island (Isla 25 Mayo), NW Antarctic Peninsula - Heredia Barión, Pablo A.; Strelin, Jorge A.; Roberts, Stephen J.; Spiegel, Cornelia; Wacker, Lukas; Niedermann, Samuel; Bentley, Michael J.; Pearson, Emma J.; Czalbowski, Nadia T. Manograsso; Davies, Sarah J.; Schnetger, Bernhard; Grosjean, Martin; et al. (Frontiers in Earth Science, 2023)
The timing and impact of deglaciation and Holocene readvances on many ice-free terrestrial continental margins of the Antarctic Peninsula have been long-studied but remain debated. Potter Peninsula on King George Island (Isla 25 de Mayo), South Shetland Islands (SSI), NW Antarctic Peninsula has a detailed assemblage of glacial landforms, geomorphological features and stratigraphic exposures for constraining deglacial landscape development and glacier readvances. Here, we present a new geomorphological map of the deglaciated foreland of the Warszawa Icefield, an outlet of the Bellingshausen (Collins) Ice Cap on Potter Peninsula based on a combination of satellite imagery and new field investigations. Results from mapping and new lithofacies analysis and chronostratigraphic data from stratigraphic sections, lake sediments and moraine deposits show that deglaciation on Potter Peninsula began before c. 8.2 ka. Around c. 7.0 ka, the Warszawa Icefield and the marine terminating Fourcade Glacier readvanced across Potter Peninsula and to the outer areas of Potter Cove. Evidence of further readvances on Potter Peninsula is then absent until Warszawa Icefield front was landward of its present position on three occasions, c. 1.7–1.4 ka, after c. 0.7 ka (most likely c. 0.5–0.1 ka), and 1956 CE. Holocene deglaciation and glacier fluctuations on Potter Peninsula are broadly coeval with other ice-free areas on the South Shetland Islands and the northern Antarctic Peninsula, and likely driven by interactions between millennial-centennial scale changes in solar insolation and irradiance, the southern westerlies, and the Southern Annular Mode.